Healthy and wholesome food education for students of Sekolah Indonesia Kuala Lumpur at the Community Learning Center, Sentul Pasar, Kuala Lumpur - Rohadi (Journal of Saintech Transfer, 2025)
The knowledge of children at the community learning center (CLC) in the Kg Chubadak Hilir area, Sentul Pasar, Kuala Lumpur, Malaysia which is under the guidance of Sekolah Indonesia Kuala Lumpur (SIKL) about healthy and nutritious food is still lacking, so it needs to be improved. Therefore, it is important to convey material related to healthy and nutritious food for elementary school age. CLC Sentul students are children aged 6-12 years from Indonesian migrant workers in Malaysia who do not have access to formal education in Malaysia. Community service was carried out on Monday (5/5/2025) at the CLC location, attended by 17 students, the material was delivered while telling stories, visual explanations, games, and video demonstrations, students were engaged in understanding the importance of consuming safe and healthy food. The purpose of international service at CLC SIKL is to increase students' knowledge of healthy and nutritious food and individual health to support student growth and development. The program was conducted in collaboration with SIKL and effectively increased students’ knowledge and awareness of healthy food, as indicated by the rise in active participation from only 1-2 students out of 17 (≈5.9-11.8%) before the session to 5-6 students (≈29.4-35.3%) after the session, reflecting an approximate increase of 24%. Feedback showed enthusiasm for healthy and wholesome food containing various nutrients from various food sources and how to recognize healthy food. This initiative highlights the effectiveness of early healthy food education in nurturing food-conscious choosing and consuming food, supporting Sustainable Development Goals (SDGs) for zero hunger and good health and well being.